Detection of Ecological Thresholds and Selection of Indicator Taxa for Epibenthic Communities Exposed to Multiple Pressures - Isabel, Laurie; Beauchesne, David; McKindsey, Chris; Archambault, Philippe (Frontiers in Marine Science, 2021)
The estuary and the Gulf of St. Lawrence (EGSL), eastern Canada form a vast inland sea that is subjected to numerous anthropogenic pressures. Management tools are needed to detect and quantify their effect on benthic communities. The aims of this study are to analyze the spatial distribution of epibenthic communities in the EGSL and quantify the impact of important pressures on them to identify indicator taxa. Epibenthic communities were sampled at 1314 EGSL sites between 2011 and 2018 by bottom trawling. Cluster analyses revealed the presence of six distinct epibenthic communities that seem to be strongly influenced by oxygen concentration. Threshold analyses confirm that oxygen is an important predictor of epibenthic community composition and distribution. A major oxygen threshold is observed around 50–100 μmol O2 L–1, resulting in a shift of community type. At these concentrations and below, opportunistic taxa dominate the community while sensitive taxa are absent or present at very low abundance. Biomass of the latter only starts to increase when oxygen concentrations reach 150 μmol O2 L–1. The species Actinostola callosa, Actinauge cristata, Ctenodiscus crispatus, and Brisaster fragilis were identified as good indicators for detecting this impact threshold forepibenthic communities. This study provides threshold-based indicator species that help to establish and monitor the ecological state of epibenthic communities in a marine ecosystem exposed to multiple pressures.